Penetapan Tersangka Pencurian Kabel Milik PT. Telkom Indonesia dalam Tahap Penyidikan (Studi Kasus di Polsek Belinyu Kabupaten Bangka) - Putri Ardila Anjelita Girsang; Rio Armanda Agustian; Rahmat Robuwan (AHKAM, 2026)
Law enforcement is the process of applying the law by law enforcement officers to ensure that the law is implemented and obeyed by all citizens. In the Indonesian context, law enforcement is based on the 1945 Constitution of the Republic of Indonesia, particularly Article 24 concerning judicial power and Article 27 concerning equality before the law, and is further regulated in the Criminal Procedure Code. This study discusses two main issues, namely the legal bases for the determination of suspect status by the police and the obstacles faced by police officers in uncovering and proving the crime of cable theft. This study aims to determine the legal basis for the determination of suspect status and the obstacles faced in the investigation process of cable theft. This study employed an empirical juridical method with a case approach through direct data collection in the field to understand the legal facts that occurred. The theoretical foundations used include law enforcement theory, evidentiary theory, and criminological theory. Data were collected through interviews, literature study, and documentation. The results showed that the determination of suspect status in the cable theft case involving property belonging to PT Telkom Indonesia by Polsek Belinyu was carried out based on the applicable criminal procedural law provisions, namely the fulfillment of at least two lawful pieces of evidence. This study also found that the obstacles in uncovering and proving the crime included the incident location having very few witnesses, the rapid disappearance of evidence, the need for expert testimony from PT Telkom Indonesia, limited facilities and infrastructure, and low public participation. These findings affirm that although the legal basis for determining suspect status has been fulfilled, the evidentiary process in practice still faces various constraints. Therefore, it is necessary to improve the professionalism of police officers, the use of technology, and better inter-agency coordination in order to realize fair and effective law enforcement.